Gender Equality in Australia: Challenging the Gender Pay Gap that Underpins Family Decisions on Paid Work and Unpaid Care - Wongsonegoro, Christopher (Business and Human Rights Law & Policy, 2025)
The disparity in average salaries between men and women in the workforce is referred to as the gender pay gap. Usually, it is computed as the percentage difference between males and women's average hourly or yearly pays. The gender pay gap is a measurement of the differential in earnings across genders and is frequently used to identify systematic biases and inequities in the labour market. It is significant to stress that the gender pay gap examines average incomes of men and women across industries, occupations, and sectors rather than comparing people in the same jobs. Factors such as occupational segregation, in which men and women often work in distinct industries and occupations, variations in educational attainment, professional advancement, and elements like discrimination and bias can all have an impact on the gender pay gap. In general, women carry a greater share of unpaid caregiving duties, such as those related to child and elder care. As a result of juggling caregiving obligations and paid labour, women's pays may be impacted due to career pauses, part-time employment, or career disruptions. This article seek to analyse to what extent the gender pay gap affects women's position in the labour market and their role in the household. It is found that the gender pay gap significantly affects family decisions about who does paid work and who does the unpaid care. The women's employment choices are influenced by the gender pay gap which causes them to give up their careers in order to fulfil unpaid caregiving obligations. Women may be more inclined to work part-time, take career vacations, or select flexible working arrangements due to lower pay, in order to accommodate caring obligations. This article proposes that companies could promote shared caregiving duties by encouraging paid parental leave for both mothers and fathers. Moreover, companies could also encourage and support flexible work schedules, to let employees balance their job and caring obligations.